(3GdGSJeQGQ hGdJZjQ aj GdSjGSI GdCeQjcjI JLGg GdbVjI GdadSWjfjI NdGd GdaJQI ef (B2012-2019 /s - (3,GMeO MSjf GMeO MSfi ahOgs; (3fhQgGf GdTjNs (2025)
(3JgOa gPg GdOQGSI Edi JMdjd GdSjGSI GdNGQLjI GdCeQjcjI JLGg GdbVjI GdadSWjfjI NdGd GdaJQI ef (B2012 (3Edi (B2019(3, eY GdJQcjR Ydi YfUQj GdGSJeQGQjI hGdJZjQ aj gPg GdSjGSI aj Xd EOGQJj GdQFjSjf ChHGeG hJQGeH(B. (3hJSYi GdOQGSI Edi GSJcTGa GdeMOOGJ GdOGNdjI hGdNGQLjI GdJj CKQJ aj UjGZI gPg GdSjGSI, hcja GfYcSJ GdJhLgGJ GdeNJdaI dcd ef ChHGeG hJQGeH Ydi WHjYI GdJYGWj GdCeQjcj eY GdbVjI GdadSWjfjI, hUhkdG Edi JMdjd (B"(3UabI GdbQf(B" (3hJbjje BKGQgG(B. (3JYJeO GdOQGSI Ydi efgLjI JMdjdjI JJfGhd GdeMOOGJ GdOGNdjI, cLeGYGJ GdeUGdM hGdQCj GdYGe hhSGFd GdEYdGe hGddhHj GdjghOj, hGdeMOOGJ GdNGQLjI, cGdeUGdM GdCeQjcjI GdMjhjI hGdSjGSjI hGdGbJUGOjI aj GdTQb GdChSW, hGdYdGbGJ eY ESQGFjd hGdOhd GdYQHjI(B. (3hJSJYQV GdOQGSI GdJWhQGJ aj GdSjGSI GdNGQLjI GdCeQjcjI NdGd aJQJj ChHGeG hJQGeH, HOkAG ef eMGhdGJ EMjGA YedjI GdSdGe aj YgO ChHGeG, Ke GdJMhd GdLPQj aj YgO JQGeH fMh OYe CcHQ dESQGFjd hJHfj QDjJgG ddUQGY, HeG aj Pdc GdGYJQGa HGdbOS YGUeI dESQGFjd hfbd GdSaGQI GdCeQjcjI, hbWY GdeSGYOGJ Yf GdSdWI GdadSWjfjI, hWQM (B"(3UabI GdbQf(B". (3ceG JMdd GdOQGSI eSJbHd eTGQjY GdJShjI GdSjGSjI aj VhA gPg GdJWhQGJ, eY GdJQcjR Ydi QOhO GdaYd GdadSWjfjI hGdYQHjI JLGg GdSjGSI GdCeQjcjI, hJbjje eOi JCKjQ (B"(3UabI GdbQf(B" (3Ydi eSJbHd GdbVjI GdadSWjfjI(B. (3hJNdU GdOQGSI Edi Cf GdSjGSI GdCeQjcjI TgOJ JZjkQG edMhkXG aj YgO JQGeH, eY GSJeQGQjI aj OYe ESQGFjd, hCf GdeMOOGJ GdOGNdjI hGdNGQLjI dYHJ OhkQG gGkeG aj JTcjd gPg GdSjGSI(B.s
This study analyzes the trajectory of U.S. foreign policy towards the Palestinian issue between 2012 and 2019, highlighting the elements of continuity and change in this policy, particularly during the tenures of two distinct American administrations: President Barack Obama's and President Donald Trump's. The study explores the internal and external determinants that have shaped this policy and how the divergent approaches of Obama and Trump impacted the nature of American engagement with the Palestinian issue, culminating in the formulation of the so-called "Deal of the Century" and an assessment of its implications.the study demonstrates that American foreign policy towards the Palestinian issue underwent significant transformations during the period 2012-2019, as it shifted from trying to revive the peace process during Obama's era to adopting an Israeli vision and working to liquidate the issue during Trump's era. The study emphasizes that internal and external determinants play a pivotal role in shaping this policy, and that there is continuity in supporting Israel, but with a change in tools and objectives. The study highlights the Palestinian and Arab reactions to this policy and their impact on the future of the Palestinian issue, ultimately concluding that the "Deal of the Century" has further complicated the crisis, and that there is an urgent need for serious international effort to find a just and comprehensive solution to the Palestinian issue that guarantees the legitimate rights of the Palestinian people.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2025. s
(3HHdjhLQGajG(B: (3UaMGJ (B118-125.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdSjGSI GdNGQLjIs -- (3GdhdGjGJ GdeJMOI GdGeQjcjIs -- (3adSWjfs; (3GddCLFhf GdadSWjfjhfs; a